MODELS FOR THE MANAGEMENT OF PERSONNEL WITHIN RAILWAY ORGANIZATIONS - Xusanova Nigora Patxullayevna; Mustayeva Guldora Salokhiddinovna (TADQIQOTLAR.UZ, 2024)
Abstract: This article endeavors to investigate and scrutinize diverse models utilized for the management of personnel within railway organizations. By conducting a thorough review of existing literature and employing a specific research methodology, the study aims to provide significant insights into the current models, their efficacy, and the ramifications for enhancing human resource practices within the railway sector. Through this comprehensive exploration, the article seeks to contribute to the existing body of knowledge, shedding light on the dynamics of personnel management in railway organizations and offering valuable implications for the optimization of human resource strategies within this specific industry context.